2006
DOI: 10.1002/ijc.22047
|View full text |Cite
|
Sign up to set email alerts
|

MUC2 expression is regulated by histone H3 modification and DNA methylation in pancreatic cancer

Abstract: Mucins are highly glycosylated proteins that play important roles in carcinogenesis. In pancreatic neoplasia, MUC2 mucin has been demonstrated as a tumor suppressor and we have reported that MUC2 is a favorable prognostic factor. Regulation of MUC2 gene expression is known to be controlled by DNA methylation, but the role of histone modification for MUC2 gene expression has yet to be clarified. Herein, we provide the first report that the histone H3 modification of the MUC2 promoter region regulates MUC2 gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
59
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(63 citation statements)
references
References 52 publications
(58 reference statements)
4
59
0
Order By: Relevance
“…It is likely based on data from other loci (29,53,54) that CTCF suppresses gene expression by recruiting a repressive complex such as the polycomb group repressor complex 2 or SIN3A and associated histone deacetylases. Consistent with these observations, previous reports showed an increase in MUC2 expression following histone deacetylase 2 depletion (19) and that expression of MUC2 was apparently dependent on H3K9 and H3K27 acetylation in the 5Ј-flanking region (55). However, our data showing that CTCF depletion increases expression of MUC2, MUC5AC, and MUC6 in different cell lines are in contrast with observations that only MUC2 and MUC5B are subject to epigenetic regulation, with MUC5AC being rarely influenced and MUC6 not at all (19).…”
supporting
confidence: 89%
“…It is likely based on data from other loci (29,53,54) that CTCF suppresses gene expression by recruiting a repressive complex such as the polycomb group repressor complex 2 or SIN3A and associated histone deacetylases. Consistent with these observations, previous reports showed an increase in MUC2 expression following histone deacetylase 2 depletion (19) and that expression of MUC2 was apparently dependent on H3K9 and H3K27 acetylation in the 5Ј-flanking region (55). However, our data showing that CTCF depletion increases expression of MUC2, MUC5AC, and MUC6 in different cell lines are in contrast with observations that only MUC2 and MUC5B are subject to epigenetic regulation, with MUC5AC being rarely influenced and MUC6 not at all (19).…”
supporting
confidence: 89%
“…Several notable CpG sites in the wider area of the MUC2 promoter region, including those in AP2 and Sp1 binding motifs, showed obvious differences in methylation level between PANC1, BxPC3, and normal colonic crypt cells (145). Similar observations showing that site-specific methylation can downregulate MUC2 gene expression have been reported in pancreatic cancer cells (142,146). These specific sites of methylation changes in the promoters may be a road map to the critically important regulatory regions of MUC2.…”
Section: Muc2: An Example Of An Epigenetically Controlled Mucin Genesupporting
confidence: 62%
“…One study examined the histone deacetylase inhibitor trichostatin A (TSA) on MUC2 expression in pancreatic cancer cell lines. Treatment with TSA resulted in the upregulation of MUC2 expression, suggesting that histone acetylation can to some degree turn on the MUC2 gene (146). In the future, further studies in other epigenetic mechanisms, including histone modification and chromatin modification in MUC2 inactivation, are expected.…”
Section: Muc2: An Example Of An Epigenetically Controlled Mucin Genementioning
confidence: 93%
“…Several studies have examined the expression of various mucin genes in relation to the nature and extent of CpG island methylation, and have found that MUC2 and MUC5B in particular, show strong correlations between promoter methylation and suppression of mucin protein synthesis. 23,[54][55][56][57] There is currently little or no evidence of methylation-induced silencing of either MUC5AC or MUC6. 23 Furthermore, MUC17, a transmembrane mucin gene, is regulated by promoter CpG island methylation and histone H3-K9 acetylation in pancreatic ductal adenocarcinomas, where promoter hypomethylation is associated with MUC17 expression.…”
Section: Discussionmentioning
confidence: 99%